THE EVOLUTION OF CONTRACTUAL LEGAL RELATIONSHIPS IN CYBERSPACE - Yakubov, Akhtam; Jurayev, Sulton (Универсальная индексная библиотека Евразийского журнала технологий и инноваций, 2023)
The digital age has brought forth a transformative shift in how contractual legal relationships are conceived, formed, and regulated. This article embarks on a comprehensive exploration of the multifaceted journey through the evolution of contractual relationships within the expansive realm of cyberspace. As the global landscape rapidly embraces digital transactions and interactions, understanding the dynamics, challenges, and adaptations of contractual relationships becomes increasingly imperative. As this article progresses, it navigates through potential future developments, emphasizing the imperative need for adaptive legal frameworks to accommodate emerging technologies and changing societal needs.